Disciplinary inquiry in dismissal from employment - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis Malaysia Sdn Bhd, 2015)
Before appropriate disciplinary action is taken against an affected worker, the employer is required to hold a domestic enquiry and observe the principle of natural justice namely, that the accused employee must be given a fair chance to challenge the charges levelled against him; to present evidence of his own choice; to cross-examine the company’s evidence; and to explain his point of view without any pressure or fear. The enquiry must be conducted before an impartial person. If the alleged misconduct is established based on evidence, the punishment imposed must be proportionate to the gravity of the misconduct. Having said the above, the issues considered in this article are as follows: (i) whether it is aprecondition for an impending dismissal on alleged gross misconduct to proceed with a disciplinary inquiry under the Industrial Relations Act 1967; and (ii) whether a dismissal without a disciplinary inquiry is illegal for non-compliance of the principles of natural justice.